The commissioning of a hybrid multi-material 3D printer. Issue 1 (October 2021) - Castellví, A; Poudelet, L; Tejo, A; Calvo, L; Uceda, R; Lustig, P; Minguella, J; Buj, I; Fenollosa, F; Krauel, L; Valls, A; Ayats, M
Abstract: Additive Manufacturing (AM) has rapidly become an important technology in both research and industry. This development has allowed the evolution of 3D printers which are able to print complex geometries at low costs and faster than traditional methods. Despite this, most of these printers are either only for using one material or one technology. This limits a lot its use in different sectors such as aeronautics, automotive or health, because multi-material prototypes are needed. For example, surgeons need surgical planning prototypes for preoperative planning. These 3D printed prototypes have mainly been manufactured using just one technology. As a result, the prototypes have some main limitations: (1) do not actually mimic the anatomical structures of the human body, (2) high costs specially for Material Jetting and Powder Bed Fusion AM technologies. Therefore, the aim of present manuscript is the design, development, and commissioning of a hybrid multi-material 3D printer.